2021
DOI: 10.3389/fsurg.2021.663364
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Management of Lung Cancer Care During Surging COVID-19

Abstract: Management of patients with lung cancer continues to be challenging during the COVID-19 pandemic, due to the increased risk of complications in this subset of patients. During the COVID-19 surge in New York City, New York University Langone Health adopted triage strategies to help with care for lung cancer patients, with good surgical outcomes and no transmission of COVID-19 to patients or healthcare workers. Here, we will review current recommendations regarding screening and management of lung cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…There were also recommendations made to supportive care, for example for the widespread use of granulocyte colony stimulating factor injections to reduce the risk of hospitalization from febrile neutropenia [ 31 ]. Consequently, more stringent measures were taken to shelter this population from contracting the virus and many scheduled treatments (i.e., chemotherapy, radiotherapy, and surgery) during the beginning of the pandemic were postponed while adaptive approaches of delivering therapy were established [ 32 , 33 ]. Cancer services rapidly developed strategies to overcome this setback and continue cancer care while minimizing the risk of COVID-19 transmission.…”
Section: Impact Of the Management Of Patients With Cancermentioning
confidence: 99%
“…There were also recommendations made to supportive care, for example for the widespread use of granulocyte colony stimulating factor injections to reduce the risk of hospitalization from febrile neutropenia [ 31 ]. Consequently, more stringent measures were taken to shelter this population from contracting the virus and many scheduled treatments (i.e., chemotherapy, radiotherapy, and surgery) during the beginning of the pandemic were postponed while adaptive approaches of delivering therapy were established [ 32 , 33 ]. Cancer services rapidly developed strategies to overcome this setback and continue cancer care while minimizing the risk of COVID-19 transmission.…”
Section: Impact Of the Management Of Patients With Cancermentioning
confidence: 99%
“…There were also recommendations made to supportive care, for example for widespread use of granulocyte colony stimulating factor injections to reduce the risk of hospitalization from febrile neutropenia [27]. Consequently, more stringent measures were taken to shelter this population from contracting the virus and many scheduled treatments (i.e., chemotherapy, radiotherapy, and surgery) during the beginning of the pandemic were postponed whilst adaptive approaches of delivering therapy were established [28,29]. Cancer services rapidly developed strategies to overcome this setback and continue cancer care whilst minimizing the risk of COVID-19 transmission.…”
Section: Impact Of the Management Of Patients With Cancermentioning
confidence: 99%
“…Postoperatively, patients should be treated in negative-pressure isolation rooms. Furthermore, the number of visitors should be drastically reduced or visitors should be prohibited altogether for patients after surgical treatment during their hospital stay [ 14 , 25 , 30 , 59 , 61 , 62 ].…”
Section: Lung Cancer Surgery In the Covid-19 Eramentioning
confidence: 99%
“…Data has also shown that patients with underlying malignancies have higher mortality rates, which estimates ranging between 3.7 and 61.5% [ 12 , 13 ]. For lung cancer, previous studies have demonstrated that lung cancer patients have higher risks of contracting COVID-19 and are significantly more likely to develop severe (respiratory) symptoms, with an estimated mortality rate of 30–50% [ 14 , 15 , 16 , 17 ]. However, despite these increased risks, the provision of quality care for cancer patients remains vital [ 18 ].…”
Section: Introductionmentioning
confidence: 99%